Design and Development of Monitoring and Controlling Claypot Compost from Household Waste Using Fuzzy Logic - Prayoga, Fery Aditya; Soelistianto, Farida Arinie; Waluyo, Waluyo; Marya, Dianthy (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Household waste production in Indonesia has seen a significant increase, rising from 64 million tons in 2016 to 70 million tons in 2020. Poorly managed waste can lead to various environmental issues, including pollution, pest outbreaks, and ecosystem damage. To address these challenges, effective waste management is crucial, with composting being chosen as one of the primary methods to reduce organic household waste. This study focuses on developing an IoT-based composting system that can monitor key parameters such as temperature, pH, and moisture, using the DS18B20 sensor for temperature, a Capacitive Soil Moisture Sensor for moisture, and a Soil pH Sensor for pH levels. The system utilizes a zero-order Sugeno-type fuzzy logic to make decisions regarding the addition of the EM4 bio activator liquid, which is necessary to maintain optimal conditions during the composting process. This method was chosen for its efficiency in handling uncertain data. Data obtained from the sensors are processed by the fuzzy logic system to determine the compost’s condition, and if needed, the bio activator liquid is added via a DC water pump controlled by a water flow sensor. Additionally, information about the compost’s condition can be accessed in real-time through a smartphone application, enabling remote monitoring. The results of this study show that the system successfully implemented zero-order Sugeno-type fuzzy logic as a decision-making tool, with an average error of 8.16%. The sensors used demonstrated high accuracy, with very low average errors: 1.31% for the pH sensor, 0.60% for the moisture sensor, and 0.53% for the temperature sensor, while the water flow sensor had an average error of 2.10%. In conclusion, the system proved effective in monitoring and controlling the addition of the bio activator liquid, thereby aiding the decomposition process by keeping the temperature, pH, and moisture parameters of the compost medium within the optimal range.